Intrafamilial Transmission of Pneumococcal Acute Spontaneous Peritonitis - Ioanna Papadatou; Angeliki Moudaki; Anastasia Mentessidou; Dimitrios Tsakogiannis; Elissavet Georgiadou; Vana Spoulou (MDPI AG, 2023)
Streptococcus pneumonia (S. pneumoniae, Pneumococcus) is a major cause of childhood morbidity and mortality worldwide. The most common presentations of invasive pneumococcal disease (IPD) in children include bacteremic pneumonia, meningitis, and septicemia. However, pneumococcal acute spontaneous peritonitis is a highly uncommon-and potentially life-threatening-presentation of invasive pneumococcal disease and should be considered in cases of abdominal sepsis. To our knowledge, we report the first case of intrafamilial transmission of pneumococcal peritonitis in two previously healthy children.